Deoxyguanosine is a TLR7 agonist. Issue 1 (14th November 2019) - Davenne, Tamara; Bridgeman, Anne; Rigby, Rachel E.; Rehwinkel, Jan
Abstract: Toll‐like receptor 7 (TLR7) is an innate immune sensor for single‐strand RNA (ssRNA). Recent structural analysis revealed that TLR7 has an additional binding site for nucleosides such as guanosine, and is activated when both guanosine and ssRNA bind. The nucleoside binding site also accommodates imidazoquinoline derivatives such as R848, which activate TLR7 in the absence of ssRNA. Here, we report that deoxyguanosine (dG) triggered cytokine production in murine bone marrow derived macrophages and plasmacytoid dendritic cells, as well as in human peripheral blood mononuclear cells, including type I interferons and pro‐inflammatory factors such as TNF and IL‐6. This signalling activity of dG was dependent on TLR7 and its adaptor MyD88 and did not require amplification via the type I interferon receptor. dG‐triggered cytokine production required endosomal maturation but did not depend on the concurrent provision of RNA. We conclude that dG induces an inflammatory response through TLR7 and propose that dG is an RNA‐independent TLR7 agonist. Abstract : Toll‐like receptor 7 (TLR7) is a pattern recognition receptor and plays important roles in virus infection and autoimmunity. TLR7 detects single‐stranded RNAs, nucleosides, and imidazoquinoline derivatives. Davenne et al. show that deoxyguanosine activates an inflammatory gene expression programme by engaging TLR7 and propose that this activity does not require RNA binding to TLR7.